A method for evaluating the salt permeability of resin materials

By partitioning liquids of different concentrations in the container and recording the quality changes after standing, the salt permeability of the resin material is simply detected, and the problem of insufficient complexity and accuracy of measuring the permeability rate of thermoplastic resins in the prior art is solved, and low cost is achieved. Permeability detection of environmentally friendly various resin materials.

CN117491245BActive Publication Date: 2024-12-17GUANGZHOU MEIYU MEDICAL LAB CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311471720.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-06
Publication Date
2024-12-17
Estimated Expiration
2043-11-06

AI Technical Summary

Technical Problem

The prior art has problems of complex operation, high cost and low accuracy when measuring the permeability rate of high-performance thermoplastic resins, especially in complex porous materials, and lack of suitable applications for a variety of scenarios. Easy way.

Method used

A simple method is used to add liquid of different concentrations on both sides of the partition container, and then weigh and record the liquid mass changes after standing to evaluate the salt permeability of the resin material. The permeability of the resin is detected by osmotic pressure difference, which is suitable for a variety of Resin material.

Benefits of technology

It realizes permeability detection of resin materials with simple operation, low testing cost and environmentally friendly, and is suitable for a variety of resin materials, and the test results are accurate and reliable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117491245B_ABST
    Figure CN117491245B_ABST
Patent Text Reader

Abstract

The present invention provides a method for evaluating the salt permeability of a resin material, the method comprising the following steps: (1) using a resin material to partition a container, adding a mass M of a1 Liquid a is added to the other side of the container with a mass of M b1 (2) After standing, weigh and record the mass M of the liquid loaded into the liquid a side. a2 , the mass of liquid loaded into the liquid b side is M b2 ; (3) According to M a1 and M a2 The size relationship of M b1 and M b2 The salt permeability of the resin material is evaluated by measuring the size relationship of the two-phase packaging material. The method for detecting the permeability of the two-phase packaging material used in the present invention is simple to operate, has low test cost, uses environmentally friendly test materials, and is applicable to a variety of resin materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of permeability testing, and in particular relates to a method for evaluating the salt permeability of a resin material. Background Art

[0002] High-performance thermoplastic resin-based composite materials have the advantages of good toughness, good impact resistance, good fatigue resistance, good wear resistance, and short molding cycle. In addition, thermoplastic prepregs have a nearly unlimited storage period at room temperature, which is more convenient to use. Combined with welding technology, thermoplastic composite materials can also achieve structural damage repair. Thermoplastic prepreg is an intermediate material for preparing thermoplastic composite materials. However, high-performance thermoplastic resins (such as PEEK) have high melt viscosity. During the preparation of prepregs, it is difficult for the resin matrix to fully penetrate into the carbon fiber bundle, which will lead to insufficient resin infiltration and uneven distribution, resulting in pores and affecting the performance of the prepreg. Resin viscosity is a parameter that changes with temperature. The higher the resin viscosity, the greater the impregnation pressure required. When the pressure is small, the resin penetration rate of the fiber is small, and it takes longer to fully impregnate the fiber; when the pressure is large, the resin penetration rate of the fiber is large, but the fiber damage will also be more serious. Temperature, pressure, and impregnation time are key process parameters that affect the quality of thermoplastic prepregs. In order to obtain high-performance thermoplastic prepregs with good appearance and internal quality, it is necessary to control the appropriate temperature, pressure and impregnation time to ensure that the resin can fully penetrate into the fiber bundle, thereby preparing qualified thermal prepregs. Therefore, it is particularly important to measure the penetration rate of resin into the fiber under different pressures.

[0003] Permeability is the degree of difficulty of a fluid passing through a porous material under a certain flow driving force, which characterizes the permeability of a porous medium to a fluid. It is a parameter related to porosity, solid particle size, distribution, particle shape and arrangement. At present, permeability is mainly obtained through three approaches: theoretical analysis, numerical simulation and experimental measurement. Among them, theoretical analysis and numerical simulation establish appropriate mathematical models for the inherent properties of porous media that play a decisive role in the direction and size of permeability, and predict the permeability of materials. However, both approaches can only predict the permeability of materials that meet specific assumptions, and cannot fully and truly describe the flow of fluids in complex porous materials. Therefore, the permeability of many complex materials needs to be measured experimentally. At present, a relatively complete permeability database for composite materials has not been established. In actual use, the permeability of the materials used is generally determined by field tests. At present, there is no special device for field tests. Most field test devices are implemented with the help of devices for measuring metal or ceramic materials, and there are errors in measurement accuracy.

[0004] CN115561138A discloses a device and method for measuring the penetration rate of resin into fibers. The device comprises: a melt module for storing and melting resin, the melt module being connected to a high-pressure gas source; a permeation module whose feed port is connected to the discharge port of the melt module, the permeation module being provided with fibers to be tested; and a heating device for heating the melt module and the permeation module. The fiber permeation rate measuring device of the method can achieve resin permeation into fibers under high pressure and high temperature, and can accurately measure the permeation pressure, time and permeation depth, so as to accurately obtain the permeation rate of resin into fibers, and the test results can be used to guide the preparation of high-performance thermoplastic prepregs.

[0005] CN112903562A discloses a resin-based composite material permeability test device, including a lower tooling, an upper tooling and a high-pressure gas cylinder. The upper and lower toolings have the same composition. The lower tooling includes a columnar structure and a flange. The flange is located on the upper surface of the columnar structure and is designed as an integrated whole with the columnar structure. A through hole is opened in the center of the flange, and a cavity that passes through from top to bottom is processed in the center of the columnar structure. The lower part of the cavity of the lower tooling is connected to the high-pressure gas cylinder through a first air pipe; the lower part of the cavity of the upper tooling is connected to a second air pipe. During the test, the test piece is placed in the central through hole of the flange of the lower tooling, and the lower tooling is inverted and placed above the upper tooling, and the flange of the upper tooling is opposite to the flange of the lower tooling, and the two are tightened by screws. A series of sensors are set on the two air pipes. The method also discloses a test method to solve the problem of permeability test of resin-based composite materials with complex pores, and provide effective support for the refined design of aircraft anti-thermal insulation under long-term flight conditions.

[0006] Therefore, developing an osmotic pressure detection method that is easy to operate and applicable to a variety of scenarios is a research focus in this field. Summary of the invention

[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for evaluating the salt permeability of a resin material, which is simple to operate, has low test cost, uses environmentally friendly test materials, and is applicable to a variety of resin materials.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for evaluating the salt permeability of a resin material, the method comprising the following steps:

[0010] (1) Use resin material to partition the container and add a mass of M to one side of the container. a1 Liquid a is added to the other side of the container with a mass of M b1 Liquid b;

[0011] (2) After standing, weigh and record the mass M of the liquid on the side filled with liquid a.a2 , the mass of liquid loaded into the liquid b side is M b2 ;

[0012] (3) According to M a1 and M a2 The size relationship of M b1 and M b2 The salt permeability of the resin material is evaluated based on the size relationship of the resin material.

[0013] Preferably, the concentrations of liquid a and liquid b are different.

[0014] In the present invention, the reason why the concentrations of liquid a and liquid b are different is to form an osmotic pressure difference between the liquids on both sides of the resin material, which is beneficial for transferring the low osmotic pressure liquid to the high osmotic pressure liquid and is convenient for detecting the permeability of the resin material.

[0015] Preferably, the liquid a and the liquid b are each independently selected from distilled water or a chloride salt solution.

[0016] Preferably, the thickness of the resin material is 0.5-5 mm, for example, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, etc.

[0017] Preferably, the M a1 With M b1 The ratio is (2-3):(2-3), for example, it can be 2:3, 1:1, 3:2, etc.

[0018] Preferably, the chloride salt solution includes any one of a sodium chloride solution, a potassium chloride solution or a calcium chloride solution.

[0019] Preferably, the mass percentage of chloride salt in the chloride salt solution is 25-30%, for example, 26%, 28%, 30%, 32%, 34%, etc.

[0020] Preferably, the resin material includes any one of polyester resin, acrylonitrile-styrene resin, polypropylene resin or polyethylene resin.

[0021] Preferably, the static ambient temperature is 35-45°C, for example, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, etc.

[0022] Preferably, the number of days for standing still is 2-10 days, for example, it can be 3 days, 4 days, 5 days, 6 days, 7 days, 8 days, 9 days, etc.

[0023] Preferably, in step (3), the standard for evaluating the salt permeability of the resin material is: if the mass of the liquid on the side with high concentration in the container increases by more than 0.05% and the mass of the liquid on the side with low concentration decreases by more than 0.4%, the resin material is judged to have salt permeability.

[0024] Preferably, the detection method comprises the following steps:

[0025] (1) Use resin material to partition the container and add a mass of M to one side of the container. a1 Liquid a is added to the other side of the container with a mass of M b1 Liquid b;

[0026] The concentrations of the liquid a and the liquid b are different; the liquid a and the liquid b are each independently selected from distilled water or a chloride salt solution;

[0027] The chloride salt solution includes any one of a sodium chloride solution, a potassium chloride solution or a calcium chloride solution; the mass percentage of chloride salt in the chloride salt solution is 25-30%;

[0028] (2) After standing at 35-45°C for 2-10 days, weigh and record the mass M of the liquid on the side filled with liquid a. a2 , the mass of liquid loaded into the liquid b side is M b2 ;

[0029] (3) According to M a1 and M a2 The size relationship of M b1 and M b2 The salt permeability of the resin material is evaluated by the size relationship; if the mass of the liquid on the side with high concentration in the container increases by more than 0.05% and the mass of the liquid on the side with low concentration decreases by more than 0.4%, it is determined that the resin material has salt permeability.

[0030] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The method for evaluating the permeability of a resin material adopted by the present invention is simple to operate, has low test cost, uses environmentally friendly test materials, and is applicable to a variety of resin materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the appearance of the container separated by polyester resin in Example 1. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0035] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0036] "Optional" or "any one" means that the subsequently described matter or event can or cannot occur, and that the description includes instances where the event occurs and instances where it does not.

[0037] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0038] The terms "one embodiment", "some embodiments", "exemplarily", "specific examples" or "some examples" described in the present invention mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this document, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0039] The sources of reagents or instruments in the following examples are as follows:

[0040] In the present invention, unless otherwise specified, percentages and contents are all based on mass. Unless otherwise specified, the experimental methods used are conventional methods, and the materials and reagents used can be purchased from commercial channels;

[0041] Polyester resin: PET, purchased from Suzhou Wujuyuan Plastic Chemical Co., Ltd., FR530BK;

[0042] Polypropylene resin: PP, purchased from Shanghai Qiaowei Chemical Technology Co., Ltd., K8025;

[0043] Polyethylene resin: product name PE, purchased from Shanghai Tingyuan Plastic Technology Co., Ltd., M2750.

[0044] Example 1

[0045] This embodiment provides a method for evaluating the salt permeability of a resin material, the method comprising the following steps:

[0046] (1) Figure 1 The container shown in the figure has a partition in the middle made of polyester resin material, saturated salt water (concentration of 26.47%) is added to one side of the container, and distilled water is added to the other side of the container;

[0047] (2) Place the container containing the two liquids at 40°C for 5 days, then weigh and record the mass of the saturated salt water and the mass of the distilled water;

[0048] (3) Based on the difference between the initial mass and the mass when discharged of saturated salt water and distilled water, the salt permeability of the polyester resin was evaluated, as shown in Table 1.

[0049] Table 1

[0050]

[0051]

[0052] According to the data in the table, when discharged, the mass of saturated salt water increases and the mass of distilled water decreases, indicating that the resin material has salt permeability.

[0053] Example 2

[0054] This embodiment provides a method for evaluating the salt permeability of a resin material, the method comprising the following steps:

[0055] (1) A container is partitioned by using polypropylene resin, a 28% potassium chloride aqueous solution is added to one side of the container, and distilled water is added to the other side of the container;

[0056] (2) Place the container containing the two liquids at 45°C for 2 days, then weigh and record the mass of the potassium chloride aqueous solution and the mass of the distilled water;

[0057] (3) Based on the difference between the initial mass and the mass when discharged of the potassium chloride aqueous solution and the distilled water, the salt permeability of the polypropylene resin was evaluated, as shown in Table 2.

[0058] Table 2

[0059] time Potassium chloride aqueous solution (g) Distilled water(g) Initial Value 58.154 49.969 45℃ constant temperature for 2 days 58.192 49.727 Difference 0.038 -0.242

[0060] According to the data in the table, when discharged, the mass of saturated salt water increases and the mass of distilled water decreases, indicating that the resin material has salt permeability.

[0061] Example 3

[0062] This embodiment provides a method for evaluating the salt permeability of a resin material, the method comprising the following steps:

[0063] (1) using polyethylene resin to partition a container, adding a 30% calcium chloride aqueous solution to one side of the container, and adding distilled water to the other side of the container;

[0064] (2) After placing the container containing the two liquids at 35°C for 10 days, weigh and record the mass of the calcium chloride aqueous solution and the mass of the distilled water;

[0065] (3) Based on the difference between the initial mass and the mass when discharged of the calcium chloride aqueous solution and distilled water, the salt permeability of the polyethylene resin was evaluated, as shown in Table 3.

[0066] Table 3

[0067] time Calcium chloride aqueous solution (g) Distilled water(g) Initial Value 58.177 49.488 35℃ constant temperature for 10 days 58.453 49.107 Difference 0.276 -0.381

[0068] According to the data in the table, the mass of saturated salt water and distilled water decreased during discharge, indicating that the resin material has salt permeability.

[0069] Example 4

[0070] This embodiment provides a method for evaluating the salt permeability of a resin material. The method is the same as that of Embodiment 1. Five polyester resin materials in the same batch are tested in parallel. The test results are shown in Table 4:

[0071] Table 4

[0072] Difference Saturated salt water (g) Distilled water(g) 1 0.647 -0.750 2 0.653 -0.753 3 0.642 -0.749 4 0.649 -0.755 5 0.645 -0.758 R(%) 0.4147 0.3674

[0073] According to the data in the table, the polyester resin was tested with saturated salt water and distilled water, and the test results were stable and the experimental repeatability was excellent.

[0074] Example 5

[0075] This embodiment provides a method for evaluating the salt permeability of a resin material. The difference between this embodiment and embodiment 1 is that the polyester resin is replaced by a polypropylene resin. Five polypropylene resin materials in the same batch are tested in parallel. The test results are shown in Table 5:

[0076] Table 5

[0077] Difference Saturated salt water (g) Distilled water(g) 1 0.247 -0.350 2 0.312 -0.451 3 0.259 -0.359 4 0.309 -0.443 5 0.261 -0.389 R(%) 3.0525 4.6742

[0078] According to the data in the table, when using saturated salt water and distilled water to test polypropylene resin, the test results are not as stable as those for polyester resin, and the experimental repeatability is slightly reduced.

[0079] Example 6

[0080] This embodiment provides a method for evaluating the salt permeability of a resin material. The difference between this embodiment and embodiment 1 is that the saturated salt water is replaced with a 28% potassium chloride aqueous solution. Five polyester resin materials in the same batch are tested in parallel. The test results are shown in Table 6:

[0081] Table 6

[0082]

[0083]

[0084] According to the data in the table, when testing polyester resin with potassium chloride aqueous solution and distilled water, the stability of the test results is not as good as that of saturated salt water and distilled water, and the experimental repeatability is slightly poor.

[0085] Example 7

[0086] This embodiment provides a method for evaluating the salt permeability of a resin material. The difference between this embodiment and embodiment 1 is that the standing temperature is adjusted to 30° C. and the standing time is 12 days. Five polyester resin materials in the same batch are tested in parallel. The test results are shown in Table 7:

[0087] Table 7

[0088] Difference Saturated salt water (g) Distilled water(g) 1 0.547 -0.853 2 0.212 -0.457 3 0.263 -0.498 4 0.139 -0.324 5 0.287 -0.430 R(%) 15.4654 20.0978

[0089] According to the data in the table, it can be seen that when testing polyester resin with a combination of saturated salt water and distilled water, it is best to leave it at 35-45°C for 2-10 days. When the temperature is too low and the standing time is too long, the stability of the test results will be reduced and the experimental repeatability will be slightly poor.

[0090] Example 8

[0091] This embodiment provides a method for evaluating the salt permeability of a resin material. The difference between this embodiment and embodiment 1 is that the standing temperature is adjusted to 50° C. and the standing time is 1 day. Five polyester resin materials in the same batch are tested in parallel. The test results are shown in Table 8:

[0092] Table 8

[0093] Difference Saturated salt water (g) Distilled water(g) 1 0.108 -0.672 2 0.305 -0.508 3 0.196 -0.257 4 0.248 -0.481 5 0.206 -0.507 R(%) 7.2545 14.8309

[0094] According to the data in the table, it can be seen that when testing polyester resin with a combination of saturated salt water and distilled water, it is best to let it stand at 35-45°C for 2-10 days. When the temperature is too high and the standing time is too short, the stability of the test results will be reduced and the experimental repeatability will be slightly poor.

[0095] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for evaluating the salt permeability of a resin material, characterized in that: The method comprises the following steps: (1) Use resin material to partition the container and add a mass M to one side of the container. a1 Liquid a is added to the other side of the container with a mass of M b1 Liquid b; (2) After standing, weigh and record the mass M of the liquid on the side filled with liquid a. a2 , the mass of liquid loaded into the liquid b side is M b2 ; (3) According to M a1 and M a2 The size relationship of M b1 and M b2 The size relationship of , and the salt permeability of the resin material are evaluated; The concentrations of the liquid a and the liquid b are different; The liquid a and liquid b are each independently selected from distilled water or a sodium chloride aqueous solution; The ambient temperature of the static state is 35-45°C; The number of days for the static placement is 2-10 days; The resin material is selected from polyester resin; In step (3), the standard for evaluating the salt permeability of the resin material is: if the mass of the liquid on the side with high concentration in the container increases by more than 0.05% and the mass of the liquid on the side with low concentration decreases by more than 0.4%, the resin material is judged to have salt permeability.

2. The method for evaluating the salt permeability of a resin material according to claim 1, characterized in that: The thickness of the resin material is 0.5-5 mm.

3. The method for evaluating the salt permeability of a resin material according to claim 1, characterized in that: The M a1 With M b1 The ratio is (2-3):(2-3).

4. The method for evaluating the salt permeability of a resin material according to claim 1, characterized in that: The mass percentage of sodium chloride in the sodium chloride aqueous solution is 25-30%.